2000
DOI: 10.1016/s0014-5793(00)01735-x
|View full text |Cite
|
Sign up to set email alerts
|

Nascent Lep inserts into the Escherichia coli inner membrane in the vicinity of YidC, SecY and SecA

Abstract: Targeting and assembly of the Escherichia coli inner membrane protein leader peptidase (Lep) was studied using a homologous in vitro targeting/translocation assay. Assembly of full-length Lep was efficient in the co-translational presence of membrane vesicles and hardly occurred when membranes were added post-translationally. This is consistent with the signal recognition particle-dependent targeting of Lep. Crosslinking experiments showed that the hydrophilic region P1 of nascent membrane-inserted Lep 100-mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
71
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 26 publications
4
71
1
Order By: Relevance
“…Consistent with this view, YidC of E. coli was shown to facilitate the Sec-independent insertion of certain membrane proteins, such as the M13 procoat, being of minor importance for the export of Sec-dependent preproteins (24,56). Nevertheless, YidC, was also shown to be associated with the Sec machinery, indicating that this protein has a more general role in membrane protein biogenesis in E. coli, for example, by catalyzing the exit of membrane proteins from the Sec translocase (23,24,57). Indications for such a lateral movement were obtained by Urbanus and co-workers (58), who showed a sequential interaction of the membrane protein FtsQ with SecY and YidC.…”
Section: Discussionmentioning
confidence: 97%
“…Consistent with this view, YidC of E. coli was shown to facilitate the Sec-independent insertion of certain membrane proteins, such as the M13 procoat, being of minor importance for the export of Sec-dependent preproteins (24,56). Nevertheless, YidC, was also shown to be associated with the Sec machinery, indicating that this protein has a more general role in membrane protein biogenesis in E. coli, for example, by catalyzing the exit of membrane proteins from the Sec translocase (23,24,57). Indications for such a lateral movement were obtained by Urbanus and co-workers (58), who showed a sequential interaction of the membrane protein FtsQ with SecY and YidC.…”
Section: Discussionmentioning
confidence: 97%
“…FtsQ is a monotopic membrane protein with an N-terminal transmembrane domain and a large C-terminal periplasmic domain. Previous studies utilized IMVs as target membranes (12,35). However, the reconstitution of such a complex process is an important step toward a detailed understanding of the minimal requirements of membrane protein insertion.…”
Section: Discussionmentioning
confidence: 99%
“…Refs. [12][13][14][15]. It has been suggested that YidC mediates the transfer of TMs from the Sec translocon into the lipid bilayer (1).…”
mentioning
confidence: 99%